Nanobiosensor for detection and quantification of DNA sequences in degraded mixed meats - Ali, Md. Eaqub; Hashim, Uda; Mustafa, Shuhaimi; Che Man, Yaakob; Mohd Yusop, Mohd Hazim; Kashif, M.; Dhahi, Thikra S.; Bari, M. F.; Hakim, M. A.; Abdul Latif, Muhammad (Hindawi Publishing Corporation, 2011)
A novel class of nanobiosensor was developed by integrating a 27-nucleotide AluI fragment of swine cytochrome b (cytb) gene to a 3-nm diameter citrate-tannate coated gold nanoparticle (GNP). The biosensor detected 0.5% and 1% pork in raw and 2.5-h autoclaved pork-beef binary admixtures in a single step without any separation or washing. The hybridization kinetics of the hybrid sensor was studied with synthetic and AluI digested real pork targets from moderate to extreme target concentrations and a sigmoidal relationship was found. Using the kinetic curve, a convenient method for quantifying and counting target DNA copy number was developed. The accuracy of the method was over 90% and 80% for raw and autoclaved pork-beef binary admixtures in the range of 5–100% pork adulteration. The biosensor probe identified a target DNA sequence that was several-folds shorter than a typical PCR-template. This offered the detection and quantitation of potential targets in highly processed or degraded samples where PCR amplification was not possible due to template crisis. The assay was a viable alternative approach of qPCR for detecting, quantifying and counting copy number of shorter size DNA sequences to address a wide ranging biological problem in food industry, diagnostic laboratories and forensic medicine.